Benign paroxysmal positional vertigo recurrence and persistence - Dorigueto,Ricardo S (2009)
Benign paroxysmal positional vertigo (BPPV) is one of the most common vestibular disorders. AIM: To study the recurrence and persistence of BPPV in patients treated with canalith repositioning maneuvers (CRM) during the period of one year. STUDY DESIGN: longitudinal contemporary cohort series. MATERIALS AND METHODS: One hundred patients with BPPV were followed up during 12 months after a treatment with CRM. Patients were classified according to disease evolution. Aquatic physiotherapy for vestibular rehabilitation (APVR) protocol was applied in cases of persistent BPPV. RESULTS: After CRM, 96% of the patients were free from BPPV's typical nystagmus and dizziness. During the follow up period of 1 year, 26 patients returned with typical BPPV nystagmus and vertigo. Nystagmus and vertigo were persistent in 4% of the patients. Persistent BPPV presented improvement when submitted to APVR. Conclusion: During the period of one year, BPPV was not recurrent in 70% of the patients, recurrent in 26% and persistent in 4%.